FORMATION OF A CULTURE OF MOTION IN THE SYSTEM OF PHYSICAL EDUCATION (EDUCATION IN THE 21ST CENTURY, 2023)
The article presents a theoretical analysis of the content of the concept of the culture ofmovement, which in modern science is presented as a multifaceted phenomenon. As a58phenomenon of general culture, the culture of movement is considered as a process of using thevalues of physical culture in various types of human motor activity.The culture of movement, as a component of physical culture, is presented as a reflection ofall its aspects.The formation of a culture of movement should be considered both as a task and as a result ofthe process of physical education.There are three levels of movement culture formation: basic, optimal and high.The analysis of scientific and methodological literature on the problem under study made itpossible to single out a number of issues that remain insufficiently studied. Further research willbe aimed at determining the criteria for assessing the level of formation of the culture ofmovement, the development of ways of its directed development in the process of physicaleducation.
Keywords: culture of movement, physical culture, education system, physical education, “school” of movements.